What a good big brother! - Landolf, Diane Wright (Random House Children's Books, 2008)
Cameron is always ready to help when his baby sister cries, whether by handing wipes to his father during a diaper change or finding the nursing pillow for his mother, until one day, when no one else can stop Sadie's tears, her big brother succeeds and gets a wonderful reward.